Maximum Torque Estimation Technique Of Three Link System For Sit To Stand Motion - Ghazali, Mohd Zaki (2018)
In Humanoid robotics field,capability to perform any task that imitates human movement has been the major research focus.Sit to stand (STS) is a very challenging motion for any humanoid robotic system.In the field of rehabilitation,it is difficult for the physiotherapist technician to readjust prosthetic leg to fit all the patient without proper knowledge and not all of them has the basic knowledge involving robotic system.Thus from several model of STS including telescopic inverted pendulum,single-link,two-link and three-link (3L),we choose to emphasize more on 3L since it is having a similar segment with human body and it fit most of the current prosthetic leg in rehabilitation centre.Current studies involving torque analysis was using a dynamic model,which is complicated and requires high computational resource to compute.Hence,the purpose of this thesis is to study the effect of mass and length’s link changes to each joint torque and much simpler equation to estimate the torque needed in short time is proposed.Simulation model were run and torque information were collected.In order to validate the equation, experiments were carried out with three-link model.Having an error with ± 0.1% proof that the results shows that there is a possibility to estimate maximum torque needed by each link with equation derive from both simulation and experiment .